2008
DOI: 10.1097/scs.0b013e318163f94d
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Maxillofacial Injuries in Motorcyclists in Malaysia

Abstract: Motorcycle casualties represent significant number in road traffic accidents in Malaysia, and among all the injuries, facial injuries pose many significant problems physiologically, functionally, and aesthetically. The aim of this study was to analyze the pattern of maxillofacial as well as other injuries in motorcyclists who were seen at Hospital Universiti Kebangsaan Malaysia.Patients' records from January 2004 to December 2005 were reviewed. Data related to demographics, vehicle/object involved in collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
39
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 11 publications
12
39
1
3
Order By: Relevance
“…This is similar to findings of studies reported from Kuala Lumpur, Malaysia 8 and Taipei, Taiwan. 13 The active nature of group which involves movement from place to place as part of job seeking, going to work or delivering services encourage their use of commercial motorcycle, a fast and cost-effective mode of transportation in developing countries.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is similar to findings of studies reported from Kuala Lumpur, Malaysia 8 and Taipei, Taiwan. 13 The active nature of group which involves movement from place to place as part of job seeking, going to work or delivering services encourage their use of commercial motorcycle, a fast and cost-effective mode of transportation in developing countries.…”
Section: Discussionsupporting
confidence: 82%
“…The higher male than female dentofacial injuries experience has been reported in several other studies. 4,8,9,11,14 Perhaps, as breadwinners for many families tend to be men, their mobility is therefore more and thereby exposed to the associated risks. This may support the observed gender trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three types of helmets can be used: fixed fullface, articulated full-face, and open-face. Not only people who do not wear helmets are 3-4 times more likely to sustain a head injury than those who do, but full-face helmets in particular seem to be mostly effective in protecting the face [7,10]. Studies on the wearing of helmets by motorcyclists in urban areas have highlighted two main points: the effectiveness of laws aimed at increasing their use and the protection provided against brain injuries and death [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of these fractures varies depending on the geographic area, socioeconomic status, and the period of investigation [1][2][3][4][5][6][7][8][9][10]. In many countries, traffic accidents are the most common cause of maxillofacial fractures [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%